Alakouluikäisten lasten moniulotteinen elämääntyytyväisyys Suomessa - Leena Haanpää; Enna Toikka; Piia af Ursin (Terveyden ja hyvinvoinnin laitos, 2026)
Lasten itsensä arvioimasta hyvinvoinnista on saatavilla vielä vähän lapsiväestöön yleistettävää tietoa, mutta sen tarve on tunnistettu. Artikkelissa tarkastellaan alakouluikäisten lasten elämääntyytyväisyyttä eri mittareilla. Tutkimuksen mukaan suomalaislasten elämääntyytyväisyys on korkealla tasolla. Käyttämällä moniulotteisia elämääntyytyväisyyden mittareita saadaan aiempaa kokonaisvaltaisempi kuva lasten hyvinvoinnista.
ENGLISH SUMMARY
Leena Haanpää & Enna Toikka & Piia af Ursin: Multidimensional life satisfaction of primary school aged children in Finland (Alakouluikäisten lasten moniulotteinen elämääntyytyväisyys Suomessa)
In focus of this article are indicators of life satisfaction that are used to measure children’s well-being. The UN Convention on the Rights of the Child (CRC), which was ratified in Finland in 1991, assures the wellbeing of all children under the age of 18. The Finnish welfare state is in an excellent position to promote a child-centred welfare policy aimed at exceeding the CRC minimum standards. This, however, requires more comprehensive data collection. Child well-being research has recognized the role of subjective well-being indicators and their significance for well-being research in general. International comparisons have shown that Finnish children of all ages rank quite highly in terms of life satisfaction. However, these results raise questions as to what conclusions can be drawn from single items that only measure life satisfaction, how children understand general life satisfaction, what are the constituent components that make up life satisfaction, and what explains life satisfaction. The most extensive Finnish surveys on child well-being mainly lean on single-item life satisfaction measures, even though there are several specific overall life satisfaction measures that have been constructed for assessing child and adolescent wellbeing.
In this study primary school-aged children’s life satisfaction and its components are explained using both single-item and multi-item indicators. The research data consist of international survey data from Children’s Worlds, the International Survey of Children’s Well- Being (ISCWeB), specifically the dataset from Finland (N=2,840). The empirical frame of life satisfaction comprises two internationally validated measures, the reduced Student’s Life Satisfaction Scale (SLSS) and Brief Multidimensional Student’s Life Satisfaction Scale (BMSLSS). Furthermore, the single-item measure Overall Life Satisfaction (OLS) is used for comparative analysis. According to the results, the use of multi-item indicators alongside single-item indicators can yield a clearer picture of children’s life satisfaction.